IMPLEMENTATION OF INTERNSHIP IN VOCATIONAL SCHOOLS AS A LEARNING PROCESS TO IMPROVE SKILLS EDUCATION IN MERANGIN DISTRICT, JAMBI PROVINCE - Alatas, Uying Hapid; Utami, Sri; Azni, Fithri; Andriani, Diyan; Setiadi, Hengky (Jendela PLS, 2024)
Apprenticeships are one of the common practices carried out by higher education institutions in Indonesia to improve learning experiences and technical skills among their students. Students who take part in the internship program are not only able to develop their professional attributes but also have the opportunity to gain professional networks and career paths. Apart from the conventional approach of connecting students with real-world work experience for a program, internships can also be applied to specific courses within a program. The article discusses the application of an internship program as a pedagogical approach in providing experiential learning in certain subjects, namely Foundations and Concrete Work. This research involved 51 second year students who were studying in the Education Department at Merangin University, Jambi in the Out-of-School Education Department. Analysis of the impact of apprenticeship experiences shows that apprenticeship programs are an effective pedagogical approach to experiential learning for basic courses and concrete work